Fluorescence intensity monitors as intensity and beam‐position diagnostics for X‐ray free‐electron lasers. (12th March 2019) - Heimann, Philip; Reid, Alexander; Feng, Yiping; Fritz, David
Abstract : A fluorescence intensity monitor has been developed for the non‐invasive, pulse‐by‐pulse normalization of LCLS‐II experiments. The linearity, noise and position sensitivity of the detectors have been characterized. Abstract : For LCLS‐II, a fluorescence intensity monitor for the non‐invasive, pulse‐by‐pulse normalization of experiments has been developed. A prototype diagnostic was constructed with a microchannel plate assembly and two photodiodes. The diagnostic was then installed in the LCLS SXR instrument Kirkpatrick–Baez mirror chamber with the detectors located above the vertically reflecting mirror. The linearity, noise and position sensitivity of the detectors have been characterized. The photodiode responsivity is suitable for high pulse energies. The microchannel plate detector shows sufficient responsivity over a wide range of pulse energies. The relative signal from the two photodiodes provides a sensitive measure of the X‐ray beam position. The fluorescence intensity monitor provides intensity normalization while being compatible with high incident power, a 0.93 MHz repetition rate and ultra‐high vacuum.